Identification of Nervosa Disease using Case-Based Reasoning - Gunung, Tar Muhammad Raja; Suri, Riko Muhammad; Purnomo, Nopi; Idaman, Akbar; Muis, Abdul (Information Technology and Science (ITScience), 2024)
Among teenagers or adults, body shape greatly affects a person's confidence. Most people will be very confident if their body shape is ideal, where the person will be very confident speaking in public. Different things with people who have a body shape that is too thin/fat, so their confidence is less to appear in public. To get the ideal body shape they will do everything possible, one of which is dieting, taking weight loss capsules, and so on. They do not know the dangers of dieting too strictly and taking weight loss capsules carelessly which can make them contract Nervosa disease. To get the results of the expert system, the case-based reasoning method will be used. After this application is built, the result obtained is the type of nervosa disease based on the symptoms felt by the user.